Counseling Stigma: A Gender Analysis of Mental Health Access in Higher Education - Irawan, Andi Wahyu; Yulindrasari, Hani; Dwisona, Dwisona (Bulletin of Counseling and Psychotherapy, 2024)
Traditional gender roles have put psychological pressure on college students. The lack of gender-sensitive counseling services and studies in universities reinforces traditional gender roles. With this basis, this study aims to determine students' views on gender-sensitive counseling services. Qualitative research using semi-structured interviews was used to understand their perspectives deeply. Focus is given to formulating questions, aiming to address potential social biases that may hinder participants from providing honest information. Participants consisted of 4 guidance and counseling students (2 men and two women) who had not received lecture material on gender-sensitive counseling in a multicultural counseling course at one of the State Universities in Samarinda City. The results showed that there is an understanding of traditional gender roles, masculinity discourse in counseling services, and gender bias occurring in counselors can be obstacles in providing access to gender-sensitive mental health services. This research confirms the need to study and design gender-sensitive counseling services to access more inclusive mental health services in higher education.